STRATIFIED APPROACH TO PREVENTION OF NO-REFLOW PHENOMENON DURING ENDOVASCULAR TREATMENT OF PATIENTS WITH ST-ELEVATION MYOCARDIAL INFARCTION - E.YU. BESSONOV; A.N. SHISHKEVICH; S.S. MIKHAYLOV; V.N. KRAVCHUK (Avicenna Tajik State Medical University, 2024)
Objective: To develop and test an algorithm for no-reflow phenomenon (NRP) prevention during endovascular treatment of patients with ST-elevation myocardial infarction (STEMI) Methods: A prospective single-center randomized study included 100 patients diagnosed with STEMI who underwent coronary artery stenting. Group 1 included 50 patients who were operated using an algorithm for the NRP prevention, while Group 2 included 50 patients who underwent routine transluminal balloon angioplasty and stenting of the coronary arteries. The NRP risk was assessed using the predictive model by Wang JW et al Results: Both groups were comparable in terms of anamnestic and clinical data, biochemical and instrumental examination results. High NRP risk was determined in 36% of Group 1 patients and 40% of Group 2 patients. NRP developed significantly less often in Group 1 patients compared to Group 2 (14% vs. 36%, p=0.01). Worsening of Killip class of acute heart failure was found significantly less common in Group 1 patients compared to Group 2 (2% versus 16%, p=0.03) Conclusion: The proposed algorithm for NRP prevention increased the effectiveness of treatment for STEMI